The Effect Of Work Division And Employee Ability On Employee Performance At Hotel Puri Lumbung Munduk Village - I Wayan Aditya Tariana; Ni Made Rianita (ARTHA SATYA DHARMA, 2022)
The purpose of this study was to determine the Division of Work affect the Performance of Employees at the Hotel Puri Lumbung Munduk Village and determine the ability of Employees to affect the Performance of Employees at the Hotel Puri Lumbung Munduk Village. Data collection techniques used in this study were questionnaires. The sampling technique used in this study is Probability sampling. The respondents used were 68 people. The data analysis technique used in this study is simple multiple regression analysis using SPSS 21 for windows.The results obtained based on the results of the study in multiple regression analysis obtained the results of the study the effect of the Division of Work (X1) on Employee Performance (Y) significant positive effect on Puri Lumbung Hotel, Munduk Village. From the results of the multiple linear regression equation it can be seen that the regression coefficient of the Work Distribution variable is 0.246 and is positive which means that if there is an increase in Work Distribution by one, it will cause an increase in Employee Performance by 0.246 assuming other variables in this equation are constant. Based on the results of the T test can be seen the value of the regression coefficient of the Division of Labor is equal to 0,000 with a significance of 0.05 and is supported by the calculation of the tcount of 4.023> from the table 1.669. While the results of the study the effect of Employee Ability (X2) on Employee Performance (Y) significantly positive effect on Puri Lumbung Hotel, Munduk Village. From the results of the multiple linear regression equation, it can be seen that the regression coefficient of the Employee Ability variable is 0.726 and is positive which means that if there is an increase in Employee Ability by one, it will cause an increase in Employee Performance by 0.726 assuming other variables in this equation are constant. Based on the results of the partial test T test data, showed that the regression coefficient of the Employee Ability variable (X2) was 0,000 with a significance of 0.05 and was supported by the calculation of the tcount of 5.195> from the table 1.669.